Spectroscopic classification and Gaia DR2 parallaxes of new nearby white dwarfs among selected blue proper motion stars - Scholz, Ralf-Dieter; Jahreiß, Hartmut (Astronomy and astrophysics, 2018)
Aims. With our low-resolution spectroscopic observing programme for selected blue proper motion stars, we tried to find new white dwarfs (WDs) in the solar neighbourhood.Methods. We used the Lépine & Shara Proper Motion (LSPM) catalogue with a lower proper motion limit of 150 mas yr−1 and the Second US Naval Observatory CCD Astrograph Catalog (UCAC2) for proper motions down to about 90 mas yr−1. The LSPM and UCAC2 photometry was combined with Two Micron All Sky Survey (2MASS) near-infrared (NIR) photometry. Targets selected according to their blue optical-to-NIR and NIR colours were observed mainly at Calar Alto. The spectra were classified by comparison with a large number of already known comparison objects, including WDs, simultaneously observed within our programme. Gaia DR2 parallaxes and colours were used to confirm or reject spectroscopic WD candidates and to derive improved effective temperatures.Results. We found ten new WDs at distances between 24.4 pc and 79.8 pc, including six hot DA WDs: GD 221 (DA2.0), HD 166435 B (DA2.2), GD 277 (DA2.2), 2MASS J19293865+1117523 (DA2.4), 2MASS J05280449+4105253 (DA3.6), and 2MASS J05005185-0930549 (DA4.2). The latter is rather bright (G ≍ 12.6) and with its Gaia DR2 parallax of ≍14 mas it appears overluminous by about 3 mag compared to the WD sequence in the Gaia DR2 colour-magnitude diagram. It may be the closest extremely low mass (ELM) WD to the Sun. We further classified 2MASS J07035743+2534184 as DB4.1. With its distance of 25.6 pc it is the second nearest known representative of its class. With GD 28 (DA6.1), LP 740-47 (DA7.5), and LSPM J1919+4527 (DC10.3) three additional cool WDs were found. Gaia DR2 parallaxes show that four of our candidates, but also two previously supposed WDs (WD 1004+665 and LSPM J1445+2527) are in fact distant Galactic halo stars with high tangential velocities. Among our rejected WD candidates, we identified a bright (G = 13.4 mag) G-type carbon dwarf, LSPM J0937+2803, at a distance of 272 pc.